What do children, parents and staff think about a healthy lifestyles intervention delivered in primary schools? a qualitative study. Issue 8 (20th August 2020) - Goldthorpe, Joanna; Epton, Tracy; Keyworth, Chris; Calam, Rachel; Brooks, Joanna; Armitage, Chris
Abstract : Objective: Primary schools are crucial settings for early weight management interventions but effects on children's weight are small and evidence shows that deficiencies in intervention implementation may be responsible. Very little is known about the roles of multiple stakeholders in the process of implementation. We used a multiple-stakeholder qualitative research approach to explore the implementation of an intervention developed to improve the diet and increase the levels of physical activity for children living in some of the most deprived areas of England. Design: For this qualitative study, interviews and focus groups were carried out using semi-structured topic guides. Data were analysed thematically. Setting: Seven primary schools (pupils aged 4 to 11) in Manchester, England. Participants: We conducted 14 focus groups with children aged 5 to 10 years and interviews with 19 staff members and 17 parents. Intervention: Manchester Healthy Schools (MHS) is a multicomponent intervention, developed to improve diet and physical activity in schools with the aim of reducing and preventing childhood obesity. Results: Three themes were developed from the data: common understandings of health and health behaviours; congruence and consistency of messages; negotiations of responsibility . Conclusion: All participant groups had a common conceptualisation of health as having physical and psychological components and that action could be taken in childhood to change behaviours that protect long-term health. When parents and staff felt a shared sense of responsibility for children's health and levels of congruence between home and school norms around diet and physical activity were high, parents and children were more likely to accept the policies implemented as part of MHS. Effective two-way communication between home and school is therefore vital for successful implementation of this intervention.